Osteosynthesis in fractures of the malleolus - Loskutov, Oleg; Loskutov, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The authors analysed treatment of 133 patients with fractures of the malleolus, 87.21 % of them being fractures of B and C types (according to AO classification). A differential tactics is suggested for stable-functional osteosynthesis of bone fractures with use of the plates, designed by the authors, for plate osteosynthesis of the external bone, these plates ensuring a more rigid fixation of fragments and an early restoration of the joint function. In osteosynthesis of the medial bone, Weber’s osteosynthesis was preferred. Tibiofibular syndesmosis in type C fractures was stabilized with two cortical screws; in other cases, stable osteosynthesis of the external bone was carried on with the suggested plates, using one blocking screw and restoring the anterior tibiofibular ligament. The complete support was allowed after 4 weeks in type A fractures and after 6–8 weeks in those of types B and C. The results, studied in compliance with Weber’s scale in 120 patients after 6–48 months, were good in 89.2 % of cases, satisfactory in 9.2 %, and unsatisfactory in 1.6 %.